Quantitative HPLC analysis of rosmarinic acid in extracts of Melissa officinallis and spectrophotometric measurement of their antioxidant activities - Canelas, Vera (2012)
We describe an HPLC experiment for the quantitative assay of rosmarinic acid in teas made from different samples. of Melissa officinalis. A spectrophotometric method employing DPPH• (2,2-diphenyl-1-picrylhydrazyl) is used to determine the antioxidant activities of the different teas. Finally an attempt is made to correlate the antioxidant properties of the different teas with their quantities of rosmarinic acid.